Investigating the role of the austenitizing temperature and cooling rate on the martensitic transformation kinetics in a SAE 9254 spring steel - Silvano Leal dos Santos; Felipe Ribeiro Toloczko; Davinson Mariano da Silva; Sydney Ferreira Santos (Journal of Alloys and Metallurgical Systems, 2024)
The effect of austenitizing temperature (ranging from 850 to 1050 °C) and cooling rates on the phase transformations were investigated, particularly when a two cooling steps protocol was adopted. It was possible to observe that the heat treatment parameters play a major role on the martensitic transformation kinetics a possible occurrence of bainitic transformation. The results indicate that a microstructure composed by small austenite grains and the formation of bainite prior the athermal martensitic transformation significantly contribute to increase the martensitic transformation rate. The Koistinen-Marburger model was employed to analyze the non-isothermal kinetics, revealing an increase in the KM and k parameters due to an increase in austenite grain size and the presence of bainite in the microstructure. The results herein demonstrate that the optimization of the heat treatment parameters is crucial to the proper control of the phases that will be present in the microstructure of the alloy, as well as the volume fraction of martensite. Thus, the accurate control of the heat treatment process is a promising approach to enhance the properties of SAE 9254 spring steel, which finds extensive use in the automotive industry.